Interactions between TNFAIP3, PTPN22, and TRAF1-C5 gene polymorphisms in patients with primary Sjögren's syndrome - Daniel Cadena-Sandoval,; Isela Montúfar-Robles,; Rosa Elda Barbosa-Cobos,; Gabriela Hernández-Molina,; Ana Karen Salas-García,; Norma Sánchez-Zauco,; Julian Ramírez-Bello, (Archives of Rheumatology, 2024)
Objectives: The aim of our study was to investigate whether TNFAIP3, PTPN22, and TRAF1-5 single nucleotide polymorphisms (SNPs) are associated with susceptibility, severity, or serological markers in primary Sjögren’s syndrome (pSS). Patients and methods: The cases and controls study was conducted between December 2021 and June 2022. TNFAIP3 rs10499194C/T, rs6920220G/A, and rs2230926T/G, PTPN22 rs2476601C/T and rs33996649G/A, and TRAF1-C5 rs10818488G/A polymorphisms were genotyped in 154 female pSS patients (mean age: 45.2±6.8 years) and 313 female control subjects (mean age: 50.3±7.5 years) using the TaqMan® SNP genotyping assay. An association analysis between TNFAIP3, PTPN22, and TRAF1-C5 SNPs and susceptibility, clinical characteristics, and serological markers of pSS was performed. Interactions between TNFAIP3, PTPN22, and TRAF1-C5 SNPs were also evaluated in patients and controls. Results: The genotype and allele frequencies showed no association with susceptibility, severity, or serological markers of pSS. Nevertheless, several interactions between TNFAIP3 and TRAF1-C5 or TNFAIP3, PTPN22, and TRAF1-C5 genotypes were associated with susceptibility to pSS (p<0.01). Conclusion: Individual TNFAIP3, PTPN22, and TRAF1-C5 SNPs are not associated with susceptibility, severity, or serological markers of pSS. However, genetic interactions between TRAF1-C5 and TNFAIP3 or TNFAIP3, PTPN22, and TRAF1-C5 SNPs are risk factors for pSS.